Analysis of incensole acetate in Boswellia species by near infrared spectroscopy coupled with partial least squares regression and cross-validation by high-performance liquid chromatography. Issue 1 (February 2020) - Rehman, Najeeb Ur; Al-Shidhani, Sulaiman; Al-Harrasi, Ahmed; Al-Rawahi, Ahmed; Mabood, Fazal; Al-Broumi, Muhammed; Al-Azri, Mohammed; Alam, Tanveer; Hussain, Javid
Incensole acetate (diterpenoid), macrocyclic cembrenoid, found in significant amounts in Boswellia papyrifera has been shown to cause anti-inflammatory, psychoactive, anxiolytic and anti-depressive effects. Boswellia is the main source of incensole acetate and therefore developing a reliable and fast method of its analysis is of high importance. Thin layer chromatography and near infrared spectroscopy coupled with partial least squares regression were used for a rapid quantification of incensole acetate in the resins of five Boswellia species. The findings showed that the acetylated fraction of Boswellia papyrifera resin (MeOH extract) yielded the maximum amount of incensole acetate (32.87%) followed by n -hexane (14.66%) and ethyl acetate (2.84%), while no incensole acetate was found in the resins from four other species. The results obtained by non-destructive NIR spectroscopy are in complete agreement with the results obtained by HPLC, suggesting that the two alternative methods provide fast quantitative analysis of incensole acetate in B. papyrifera .